2018
DOI: 10.1016/j.ygcen.2017.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid programming of neuroimmune function

Abstract: Throughout life physiological systems strive to maintain homeostasis and these systems are susceptible to exposure to maternal or environmental perturbations, particularly during embryonic development. In some cases, these perturbations may influence genetic and physiological processes that permanently alter the functioning of these physiological systems; a process known as developmental programming. In recent years, the neuroimmune system has garnered attention for its fundamental interactions with key hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 150 publications
0
28
0
Order By: Relevance
“…These receptors belong to the superfamily of nuclear receptors and act as ligand‐activated transcription factors, regulating gene expression by binding to specific DNA‐responsive elements. Although the regulation by HPGC of the genes here evaluated has not yet been described, it is already known that the expression of ATF3, c‐fos, GFAP, Iba1, IL‐1β and TNFα can be regulated by PR‐ and/or GR‐dependent mechanisms, thus enabling their regulation by the steroid.…”
Section: Discussionmentioning
confidence: 99%
“…These receptors belong to the superfamily of nuclear receptors and act as ligand‐activated transcription factors, regulating gene expression by binding to specific DNA‐responsive elements. Although the regulation by HPGC of the genes here evaluated has not yet been described, it is already known that the expression of ATF3, c‐fos, GFAP, Iba1, IL‐1β and TNFα can be regulated by PR‐ and/or GR‐dependent mechanisms, thus enabling their regulation by the steroid.…”
Section: Discussionmentioning
confidence: 99%
“…However, the postnatal period represents a more critical period for HPA axis maturation in most mammals and some bird species (Kapoor et al, 2006;Sims and Holberton, 2000;Wada et al, 2009), when both CORT and cortisol are present in equal amounts (Jenkins and Porter, 2004). As the effects of developmental stress can vary depending on the duration of early stress exposure, more work is required to establish any vulnerable windows of sensitivity to prenatal elevations in glucocorticoids (Walker and Spencer, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, (2) prenatal CORT may prolong the immediate immunosuppressive state typically observed in animals exposed to stress in the short term (Dimatelis et al, 2012;Wei et al, 2012). The importance of this is that developmental stress may program different neuroimmune responses depending on the developmental stage at which an individual is exposed to stress, the type of stressor experienced and the quality of the environment to which the individual is exposed in later life (Walker and Spencer, 2018). Such effects may be adaptive or transmitted through generations (Ericsson et al, 2016;Grindstaff et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, studies with mammals have reported that exposure to maternal glucocorticoids, due to prenatal stress, may generate deleterious effects in the lung, as reduced lung function, increased lung inflammation and airway hyperreactivity [8][9][10][11]. Nonetheless, mechanisms related to lung glucocorticoid exposure of the offspring during gestation have not yet been well elucidated, although it is well known that glucocorticoid receptors (GR) function is fundamental for the maintenance of several physiological effects [6,12].…”
Section: Introductionmentioning
confidence: 99%